Strategic and Growth Orientation to Improve Performance of B2B SMEs in Emerging Markets - Dell Fereira, Hellen; Hirvon, Gabriele; Sanchy, Dwork Sanchy (Inovasi Analisis Data, 2024)
Purpose: We do this with offering a study of the influence of strategic orientations, entrepreneurial orientation (EO), Growth orientation (GO), Market orientation (MO), and Brand orientation (BO) on performance of B2B SMEs in forming economies, in this case in Chile, Peru and Moldova. The aim is to explore how these orientations promote innovation and support firm performance.Method: The paper adopts a quantitative methodology using survey data from 300 B2B SMEs sampled from the three nations. Structural Equation Modeling (SEM) was utilized to investigate both direct and indirect relationships, as well as the mediating effect of Brand Orientation on the relationship between strategic orientations and performance.Findings: The findings show that Entrepreneurial Orientation (EO) and Growth Orientation (GO) are significant predictors of Brand Orientation (BO), which leads to better performance in the firms. Market Orientation (MO)1 is the key to integrating company strategies with consumer needs, which in turn bolsters performance. Brand orientation plays a key mediating role within the nexus of strategic orientations and performance.Novelty: This paper adds to the existing literature by presenting the mediating role of Brand Orientation in B2B SMEs of emerging economies. It offers an aligned vision of how distinct strategic orientations interrelate to improve firm performance across heterogeneous market contexts.Implications: The findings suggest B2B SMEs managers in emerging markets ought to build a strong Brand Orientation alongside their Entrepreneurial and Growth Orientations. It is recommended that policymakers enable the provision of supportive environments that nurture entrepreneurial ventures, as well as accessibility to relevant services that propel innovation and responsiveness to markets. This facilitates better efficacy and competitiveness in the international environment.